Fosmetpantotenate Randomized Controlled Trial in Pantothenate Kinase–Associated Neurodegeneration. Issue 6 (16th November 2020) - Klopstock, Thomas; Videnovic, Aleksandar; Bischoff, Almut Turid; Bonnet, Cecilia; Cif, Laura; Comella, Cynthia; Correa‐Vela, Marta; Escolar, Maria L.; Fraser, Jamie L.; Gonzalez, Victoria; Hermanowicz, Neal; Jech, Robert; et al.
Abstract: Background: Pantothenate kinase–associated neurodegeneration (PKAN) currently has no approved treatments. Objectives: The Fosmetpantotenate Replacement Therapy pivotal trial examined whether treatment with fosmetpantotenate improves PKAN symptoms and stabilizes disease progression. Methods: This randomized, double‐blind, placebo‐controlled, multicenter study evaluated fosmetpantotenate, 300 mg oral dose three times daily, versus placebo over a 24‐week double‐blind period. Patients with pathogenic variants of PANK2, aged 6 to 65 years, with a score ≥6 on the PKAN‐Activities of Daily Living (PKAN‐ADL) scale were enrolled. Patients were randomized to active (fosmetpantotenate) or placebo treatment, stratified by weight and age. The primary efficacy endpoint was change from baseline at week 24 in PKAN‐ADL. Results: Between July 23, 2017, and December 18, 2018, 84 patients were randomized (fosmetpantotenate: n = 41; placebo: n = 43); all 84 patients were included in the analyses. Six patients in the placebo group discontinued treatment; two had worsening dystonia, two had poor compliance, and two died of PKAN‐related complications (aspiration during feeding and disease progression with respiratory failure, respectively). Fosmetpantotenate and placebo group PKAN‐ADL mean (standard deviation) scores were 28.2 (11.4) and 27.4 (11.5) at baseline, respectively, and were 26.9 (12.5) and 24.5 (11.8) at week 24, respectively. The difference in least square mean (95% confidence interval) at week 24 between fosmetpantotenate and placebo was −0.09 (−1.69 to 1.51; P = 0.9115). The overall incidence of treatment‐emergent serious adverse events was similar in the fosmetpantotenate (8/41; 19.5%) and placebo (6/43; 14.0%) groups. Conclusions: Treatment with fosmetpantotenate was safe but did not improve function assessed by the PKAN‐ADL in patients with PKAN. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.